Analisis Putusan Mahkamah Konstitusi yang Melampaui Batas Kewenangan dalam Putusan Nomor 124/PUU-XXIII/2025 tentang Pemisahan Pemilu Nasional dan Pemilu Lokal - Rezki Amalia; Ahmad Rustan; Nur Nashriyani Jufri (Jurnal Hukum Lex Generalis, 2025)
This study analyzes Constitutional Court Decision Number 124/PUU-XXIII/2025, which divides the conduct of elections into national elections and local elections. This study uses a normative legal research method employing two approaches: the statutory approach and the case approach. The results of the study show that the decision not only interprets constitutional provisions but also brings substantive effects that change the election cycle and potentially conflict with Article 22E of the 1945 Constitution concerning simultaneous elections. Compared to Decision 135/PUU-XXII/2024, Decision 124 further expands the substance to resemble judicial legislation. This study emphasizes the need to limit the authority of the Constitutional Court and strengthen checks and balances mechanisms to prevent ultra petita and maintain the legitimacy of democracy. Recommendations are directed towards the renewal of election policies that are consistent with the principles of LUBER JURDIL and ensure legal certainty and accountability election administration